DEVELOPMENT OF A MAGLEV TRAIN’S CARRIAGE’S DYNAMIC’S MODEL CONSTRUCTING ALGORITHM - Polyakov, V. О.; Poslavsky, S. Yu. (Systems and Technologies, 2025)
The main requirements for a system dynamics model are: relevance, effectiveness, reliability, cost-effectiveness, systematicity, accessibility for review, and informativeness. To the greatest extent, models obtained using tensor methods meet these requirements. The nature of the problems, in the solution of which it is planned to use the developed methodology, as well as the structure of their object of study, indicate that an aggregate of mechanical and electromagnetic inertial elements that interact through flexible ones can be adopted as its calculation scheme. The aim of the research was to further develop the method of maglev train's motion's tensor modeling using the example of its carriage, taking into account the presence of mechanical and electromagnetic elements which determine its movement. Before being combined into an aggregate, which is accepted as the design scheme of the object under consideration, the supporting elements of this scheme are not connected in any way, their movements are not restricted in any way. After coupling, constraints are imposed on the movements of the elements, which are reflected by the bond equations. The structure of an aggregate is described by its structural matrix. The design scheme of the carriage is an aggregate of ideal inertial elements connected according to a structural matrix. The motions of both a separate support body and their non-conjugated conglomerate are described by tensor equations. To take into account the structure of a wagon's calculation scheme, the equations describing the movements of an unconnected set of support bodies are convoluted with the structural matrix of the unit. The resulting carriage's dynamics model is also tensor and can be easily converted to another coupling structure by convolution with the transition matrix from the previous support body coupling structure to the next. The basis for building a carriage's motion model is the equations describing the dynamics of the supporting bodies, as well as the structural matrix of the unit, which reflects its structure. Such a model meets the requirements of holistic consideration of both the parametric and structural organization of the object under consideration. The developed methodology for its construction can be successfully used when researching such trains dynamics.